Spatial prediction based on self-similarity compensation for 3D holoscopic image and video coding - Conti, C.; Lino, J.; Nunes, P.; Soares, L. D.; Correia, P. L. (18th IEEE International Conference on Image Processing, 2011)
Holoscopic imaging, also known as integral imaging, provides a solution for glassless 3D, and is promising to change the market for 3D television. To start, this paper briefly describes the general concepts of holoscopic imaging, focusing mainly on the spatial correlations inherent to this new type of content, which appear due to the micro-lens array that is used for both acquisition and display. The micro-images that are formed behind each micro-lens, from which only one pixel is viewed from a given observation point, have a high cross-correlation between them, which can be exploited for coding. A novel scheme for spatial prediction, exploring the particular arrangement of holoscopic images, is proposed. The proposed scheme can be used for both still image coding and intra-coding of video. Experimental results based on an H.264/AVC video codec modified to handle 3D holoscopic images and video are presented, showing the superior performance of this approach.